Psychology of sustainability and sustainable development in organizations - Fabio, Annamaria Di; Fabio, Annamaria Di; Cooper, Cary L..; Routledge Imprint of Taylor and Francis group (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"This volume answers calls for improving sustainability and sustainable development in organizations from a psychological point of view. It offers a range of perspectives on the current research in the psychology of sustainability and sustainable development, to highlight effective ways of improving the well-being and healthy sustainable development in organizations"--
Includes bibliographical references and index.
Keywords: Organizational behavior; Sustainability -- Psychological aspects; Sustainable development -- Psychological aspects; Organizational change; Psychology Of Sustainability and Sustainable Development In Organizations